Small Group Discussion Strategy Towards Students’ Reading Comprehension of SMA Negeri 11 Bulukumba - Agus Rahmat (Metathesis: Journal of English Language, Literature, and Teaching, 2017)
The objective of this research was to find out the effectiveness of Small Group Discussion Strategy in improving the students’ reading comprehension ability at the Eleventh Grade Students of SMA Negeri 11 Bulukumba. This research employed quasi experimental design with pre-test and post-test design. There were two variables; they are independent variable (Small Group Discussion Strategy) and dependent variable (the students’ reading comprehension). The population of this research was the Eleventh Grade Students of SMA Negeri 11 Bulukumba in academic year 2013/2014 which consisted of 122 students. The researcher took 56 students as the sample of the research with 28 students as experimental class in XI IPA 1 and 28 students as control class in XI IPA 2. The sample was selected by using purposive sampling. The instrument of this research was a written testused in pre-test and post-test. The result of the data indicated that there was a significant difference between students’ post-test in experimental class and controlled class. The mean score of post-test (77.3) in experimental class was greater than the mean score of post-test (71.9) in controlled class and from t-test, the researcher found that the value of t-test (3.176) was greater than t-table (2.000) at the level of significances. It means that this is a significant difference between the result of the students’ pre-test and post-test. Therefore, H0 was rejected and H1 was accepted. Based on the finding and discussion of the research, the researcher had drawn a conclusion that the use of Small Group Discussion Strategy in Improvingthe student’s reading comprehension at the Eleventh Grade Students of SMA Negeri 11 Bulukumba was effective.